2015
DOI: 10.18632/oncotarget.6420
|View full text |Cite
|
Sign up to set email alerts
|

Luminal long non-coding RNAs regulated by estrogen receptor alpha in a ligand-independent manner show functional roles in breast cancer

Abstract: Estrogen Receptor alpha (ERα) activation by estrogenic hormones induces luminal breast cancer cell proliferation. However, ERα plays also important hormone-independent functions to maintain breast tumor cells epithelial phenotype. We reported previously by RNA-Seq that in MCF-7 cells in absence of hormones ERα down-regulation changes the expression of several genes linked to cellular development, representing a specific subset of estrogen-induced genes. Here, we report regulation of long non-coding RNAs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 48 publications
9
80
0
1
Order By: Relevance
“…In contrast, HOTAIR was not among the 20 lncRNAs identified as upregulated and 9 downregulated by "apo-ERα" (non-ligand-occupied ERα) in a bioinformatic analysis of BCa cell lines and tumor tissues with experimental follow-up in MCF-7 cells (Miano et al 2016). That study identified DSCAM-AS1 as the most apo-ERα upregulated lncRNA and its expression was higher in luminal A and B breast tumors compared to normal breast, HER2+, or basal-like tumors.…”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast, HOTAIR was not among the 20 lncRNAs identified as upregulated and 9 downregulated by "apo-ERα" (non-ligand-occupied ERα) in a bioinformatic analysis of BCa cell lines and tumor tissues with experimental follow-up in MCF-7 cells (Miano et al 2016). That study identified DSCAM-AS1 as the most apo-ERα upregulated lncRNA and its expression was higher in luminal A and B breast tumors compared to normal breast, HER2+, or basal-like tumors.…”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 90%
“…This review is not comprehensive with respect to lncRNAs in endocrine-related cancers, but summarizes representative lncRNAs that are bestcharacterized ( Table 2 and described below). Examples of recent reviews of lncRNAs include roles in: female reproductive cancers (Ong, et al 2017), BCa (Malih, et al 2015;Miano, et al 2016;Niknafs, et al 2016;Venkatesh et al 2015;Warburton and Boone 2017), prostate cancer (PCa) (Alahari, et al 2016;, and thyroid cancer (Murugan, et al 2017).…”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…By RNA-seq in breast cancer cell lines, two recent studies identified lncRNAs regulated by the ER in the presence or absence of an estrogen agonist ( 43 , 44 ). However, we found only two lncRNAs (DSCAM-AS1 and RP11-161M6.2) that overlap with our ER-related signature and also between these two studies themselves, suggesting differential mechanism between cell lines and tissues and/or specificities related to the method/platform used.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of DCCAM-AS1 promoted growth in the absence of estrogen indicating a possible role in tumor progression and tamoxifen resistance [82]. DDCAM-AS1 was found by another group to be the most abundant lncRNA of 133 that are regulated by ligand-independent ERα activity, further suggesting a role in tamoxifen resistance [83]. …”
Section: Global Analyses Reveal Widespread Dysregulation Of Lncrmentioning
confidence: 99%